Method and validity of transcranial sonography in movement disorders - Skoloudík, David; Walter, Uwe (International review of neurobiology, 2010)
Transcranial sonography (TCS) of the brain parenchyma in patients with movement and other neurodegenerative disorders has developed with increasing dynamics during the past two decades. The specific advantages of TCS are the different visualization of brain structures compared to other neuroimaging methods due to the different physical imaging principle, high-resolution imaging of echogenic deep brain structures, on-time dynamic imaging with high resolution in time, relatively low costs of technical equipment, wide availability, short investigation time, noninvasivity, mobility and bedside availability, and little corruption by patients' movements. TCS proved sensitive and reliable in detecting disease-specific alterations of brainstem structures and basal ganglia in various movement disorders. Here, we give an overview on the technical requirements and recommendations on the standardized application of TCS of deep brain structures in movement disorders. We discuss methodological potentials and limitations of TCS, its validity, and future developments.
Keywords: diferenciální diagnóza; ultrasonografie dopplerovská transkraniální; Diagnosis, Differential; Reproducibility of Results; pohybové poruchy; prediktivní hodnota testů; Ultrasonography, Doppler, Transcranial; Humans; Movement Disorders; reprodukovatelnost výsledků; lidé; Predictive Value of Tests